The Machine behind the Stage: A Neurobiological Approach toward Theoretical Issues of Sensory Perception - Moutoussis, Konstantinos (Frontiers in Psychology, 2016)
The purpose of the present article is to try and give a brief, scientific perspective on several issues raised in the Philosophy of Perception literature. This perspective gives a central role to the brain mechanisms that underlie perception: a percept is something that emerges when the brain is activated in a certain way and thus all perceptual experiences (whether veridical, illusory, or hallucinatory) have a common cause behind them, namely a given brain-activation pattern. What distinguishes between different cases of perception is what has caused this activation pattern, i.e., something very separate and very different from the perceptual experience itself. It is argued that separating the perceptual event from its hypothetical content, a direct consequence of the way everyday language is structured, creates unnecessary ontological complications regarding the nature of the hypothetical ‘object’ of perception. A clear distinction between the physical properties of the real world on the one hand (e.g., wavelength reflectance), and the psychological properties of perceptual experiences on the other (e.g., color) is clearly made. Finally, although perception is a way of acquiring knowledge/information about the world, this acquisition should be considered as a cognitive process which is separate to and follows perception. Therefore, the latter should remain neutral with respect to the ‘correctness’ or ‘truth’ of the knowledge acquired.